Establishment of a Sonotrode Ultrasound-Assisted Extraction of Phenolic Compounds from Apple Pomace - María del Carmen Razola-Díaz; María José Aznar-Ramos; Eduardo Jesús Guerra-Hernández; Belén García-Villanova; Ana María Gómez-Caravaca; Vito Verardo (Foods, 2022)
Apple pomace is the main by-product from apple processing in the juice industry and is considered a source of polyphenols with several health bioactivities. Thus, this research focuses on the establishment of the ultrasound-assisted extraction of total phenolic compounds, focusing on phloretin and phloridzin, with high antioxidant activity from apple pomace, using a sonotrode. We used a Box–Behnken design of 15 experiments with 3 independent factors (ethanol (%), time (min) and amplitude (%)). The responses evaluated were the sum of phenolic compounds, phloretin and phloridzin measured by HPLC–MS-ESI-TOF, and antioxidant activity measured by DPPH, ABTS and FRAP. The validity of the model was confirmed by ANOVA. Further, it was carried out using a comparison between different apple pomaces with or without seeds extracted by the optimal conditions. Phloretin and phloridzin accounted for 7 to 32% of the total phenolic compounds in the apple pomaces. Among all the apple pomace analyzed, that of the variety Gala had the highest phenolic content and antioxidant activity. The presence of the cyanogenic compound amygdalin was detected in apple pomaces that contained seeds accompanied with a higher content of phloretin and phloridzin but a lower content of flavan-3-ols.